Real-time ultrasound evaluation of CORE muscle activity in a simultaneous contraction in subjects with non-specific low back pain and without low-back pain. Protocol of an observational case-control study - Cervera-Cano, María; Sáez-García, María Carmen; Valcárcel-Linares, David; Fernández-Carnero, Samuel; López-González, Luis; Gallego-Izquierdo, Tomás; Pecos-Martin, Daniel (PloS one, 2023)
Non-specific low back pain represents 90–95% of all cases of low back pain and it has a prevalence of 18% in the adult population, assuming a great socioeconomic impact. The main objective of this observational case-control study study is to evaluate if there are differences in the simultaneous contraction of the core muscles between nonspecific low back pain and healthy subjects. This study will be carried out in the Physiotherapy department of the University of Alcalá. Eighty-two participants <18 years old, will be recruited, paired with NSLBP (n = 41) and healthy (n = 41). The main outcome will be the onset muscle contraction of lateral abdominal wall (internal oblique, external oblique and transversus abdominis), pelvic floor, lumbar multifidus and respiratory diafragm. The maneuvers that the subjects will perform will be abdominal drawing in maneouver, contralateral arm lift, valsalva, and voluntary pelvic floor contraction in sitting and standing. As a secondary objective, to analyze the amount of contraction of each muscle group and the capacity of the diaphragms to be excreted in both groups of subjects. Finally, to relate pain and disability.